Application of The Big Five Personality Test in Designing Lecturer Recruitment and Selection: Application of The Big Five Personality Test in Designing Lecturer Recruitment and Selection - Febriansah, Rizky Eka; Firdaus, Vera; Junaedi , Muhammad (Procedia of Social Sciences and Humanities, 2022)
Recruitment are steps in searching, finding, bringing in, and ensuring a number of individuals from outside and from within the company as candidates for workforce with certain privileges in accordance with the designated of the organization's human resource policies. HR placement is planned so that the organization can maximize the capabilities of the individual in order to achieve the goals of the organization's goals. In order for recruitment and placement of human resources to run better and produce candidates who are more competent and able to adapt more quickly to organizational culture, the Myers - Briggs personality test can be a solution in finding employee candidates. Through this test, the University is able to find out the personality types of employee candidates, so that Universitas Muhammadiyah Sidoarjo can find employee candidates who are in line with the organizational vision and mission, and as well as candidates who are energetic and / or willing to be active in the union.This study uses an analytical technique in the form of an interactive analysis model with the Universitas Muhammadiyah Sidoarjo as the object of research, where all permanent employees who work in the office of the University of Muhammadiyah Sidoarjo campus 1 are the samples.